Experimental and numerical study on vibration and structure-borne noise of high-speed railway composite bridge. (April 2022) - Gu, Yi-Wei; Nie, Xin; Yan, Ai-Guo; Zeng, Jia-Hua; Liu, Yu-Fei; Jiang, Yue-Xin
Highlights: A 5 × 50 m continuous steel–concrete composite bridge for high-speed railway is introduced. The train-induced vibration response and radiated noise of the bridge were measured. The prediction model of vibration and structure-borne noise of the bridge is established. The dominant frequency range of structural vibration and noise of composite bridge is 20 ∼ 1000 Hz. The acceleration level and radiated noise are increased after removing the bottom concrete. Abstract: In order to investigate the characteristics of train-induced vibration and structure-borne noise of high-speed railway steel–concrete composite bridge, a 5 × 50 m continuous steel–concrete composite bridge is adopted and tested in this paper. The vibration acceleration response and radiated noise of the bridge are measured during the test. The prediction model of vibration and structure-borne noise is further established to explore the radiation spectrum characteristics of the composite bridge. Firstly, the train-track-bridge dynamic interaction theory is applied to calculate the vibration response of the bridge under high-speed train loading. The boundary element method (BEM) and Statistical Energy Analysis (SEA) are subsequently combined to predict the full-frequency band noise of the structure. The accuracy of the model is verified through comparison with the measured data. Based on the field test and numerical study, it is found that the dominant frequency range of vibration and structure-borne noise is 20 ∼ 1000 Hz. The root mean square (RMS) accelerations of vertical and transverse vibration are lower than 0.5 m/s 2, while local vibration of the steel web can reach 1.0 ∼ 2.5 m/s 2 . As a result, the acoustical contribution of the web at far-field site can reach 80% of the structure-borne noise. In addition, the setting of the bottom concrete reduces the acceleration level of the bottom plate by 10.75 dB and the radiated noise by 7.16 dB, showing a good effect of vibration and noise reduction.